2016
DOI: 10.3171/2016.2.peds15628
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging study of pediatric patients with congenital hydrocephalus: 1-year postsurgical outcomes

Abstract: OBJECTIVE The purpose of this study was to investigate white matter (WM) structural abnormalities using diffusion tensor imaging (DTI) in children with hydrocephalus before CSF diversionary surgery (including ventriculoperitoneal shunt insertion and endoscopic third ventriculostomy) and during the course of recovery after surgery in association with neuropsychological and behavioral outcome. METHODS This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…A recent study published by our group showed that DTI was sensitive in detecting underlying WM changes and correlated highly with improved neurocognitive outcomes after a 6-week iPad application-based occupational therapy intervention in school age children with stable, surgically treated hydrocephalus earlier in life [72] . This study further supports that, when followed longitudinally over time, the DTI parameters may serve to correlate functional outcomes in a similar way to serial head circumference measurements in infants and toddlers to help predict normal development or possible impending clinical pathology [55] .…”
Section: Dti and Surgically Treated Pediatric Hydrocephalussupporting
confidence: 51%
See 4 more Smart Citations
“…A recent study published by our group showed that DTI was sensitive in detecting underlying WM changes and correlated highly with improved neurocognitive outcomes after a 6-week iPad application-based occupational therapy intervention in school age children with stable, surgically treated hydrocephalus earlier in life [72] . This study further supports that, when followed longitudinally over time, the DTI parameters may serve to correlate functional outcomes in a similar way to serial head circumference measurements in infants and toddlers to help predict normal development or possible impending clinical pathology [55] .…”
Section: Dti and Surgically Treated Pediatric Hydrocephalussupporting
confidence: 51%
“…In order to further clarify and establish the use of DTI in the management of childhood hydrocephalus, Mangano et al [55] recently published the first multicenter, prospective, longitudinal imaging study of pediatric hydrocephalus investigating both imaging and behavioral outcomes prior to (at baseline) and after surgical management. The study included 54 patients with congenital hydrocephalus who underwent surgery and 64 normal controls.…”
Section: Dti and Surgically Treated Pediatric Hydrocephalusmentioning
confidence: 99%
See 3 more Smart Citations